O brincar da criança indígena Sateré-Mawé: elo entre a socialização e a formação cultural - (:unkn) unknown (Universidade Federal do Amazonas, 2015)
The present research presents the socializing process and cultural formation on the play of the Sateré-Mawé child, basing on the empiric investigation in the Michilles island community at Maués/AM. Our main objective is to analyze the relationship of the play of the Satere-Mawé child with meanings of social and cultural behavior through childhood formation and pedagogical process of the local school. As specific objectives, we characterize and discuss the social and cultural relations between children and adults in both group perspectives; how children understand the playing and adults opinion about children formation. In addition, we analyze the social and cultural meaning of indigenous playing by considering it as a infantile cultural expression. Our methods were based on direct observation from field work along with open interviews, oral reports, photographs, and secondary references. Based on our results, we could conclude that the building process of the play of the Sateré children from Micheles Island reflects the daily routine, comprehension, experimentation, and cultural formation from the social activities into the thoughts of the community. At the same time, inside this process there is a rebuilding of the cultural heritance with intercultural relationships.
Keywords: Formação Cultural; Socialização; Criança Sateré-Mawé; Jogos e Brincadeiras; Cultural Formation; Socialization; Child Sateré-Mawé; Games and Plays; CIÊNCIAS HUMANAS: EDUCAÇÃO